Scanning System Optimum Control Principles - Gelezevicius, V. (Elektronika ir Elektrotechnika, 1997)
The optimum control methods of scanning systems stepping drives, enabling to form their actuating torque as a function of defined step value and shuttle drive reverse time are proposed and investigated. Two principles of embodiment of these methods, using the shuttle drive velocity in reverse zone as a control function of the stepping drive motor current or velocity are proposed. For compensation of loading torque influence on the accuracy of the stepping drive positioning process, a control method, based on reference model adaptive control principle is proposed. The results of modelling are given.